2021
DOI: 10.1007/s00167-020-06399-2
|View full text |Cite
|
Sign up to set email alerts
|

Suture tape augmentation ACL repair, stable knee, and favorable PROMs, but a re-rupture rate of 11% within 2 years

Abstract: Purpose The aim of this study is to investigate clinical and magnetic resonance imaging (MRI) outcomes after anterior cruciate ligament (ACL) repair using the suture tape augmentation (STA) technique. Methods This prospective interventional case series included 35 patients who underwent STA ACL repair and were all followed up for 2 years. The ACL rupture was between 4 and 12 weeks old and per-operatively conirmed repairable. The International Knee Documentation Committee (IKDC), and Lysholm and Tegner scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Higher failure rates were also generally observed in younger patients after ACL reconstruction and were attributed to higher activity levels. In keeping with this, Heusdens et al 12 reported that a preoperative Tegner score 7 was a risk factor for failure after ACL repair. Despite this, the higher failure rate in young patients appeared to be more pronounced after repair than reconstruction.…”
Section: Discussionmentioning
confidence: 72%
“…Higher failure rates were also generally observed in younger patients after ACL reconstruction and were attributed to higher activity levels. In keeping with this, Heusdens et al 12 reported that a preoperative Tegner score 7 was a risk factor for failure after ACL repair. Despite this, the higher failure rate in young patients appeared to be more pronounced after repair than reconstruction.…”
Section: Discussionmentioning
confidence: 72%
“…To date, many studies have been published on biomechanics after ACL-R as summarised in several systematic reviews, [17][18][19][20][21][22][23] yet only few studies have reported on gait analysis (with a simple marker model) and functional hop testing in patients after ACL repair and dynamic intraligamentary stabilisation (DIS) (Ligamys). 24 25 While Leister et al 26 reported comparable single leg hop performance after primary ACL repair with InternalBrace augmentation and after ACL-R and the few available reviews and casecontrol studies on small numbers of patients have shown promising results regarding clinical outcomes, [27][28][29][30][31][32] to date, comprehensive clinical, socioeconomic and functional-biomechanical analyses after this procedure are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Suture anchors were used in two studies for the femoral fixation of proximal tears [ 42 , 62 ]. Interestingly, all studies published since 2019 applied an internal brace as suture tape augmentation [ 18 , 25 , 42 , 62 ], a technique which is also used to repair ACL ruptures [ 5 , 19 , 20 , 67 ]. This highlight how the promising results of modern ACL repair have sparked a renewed interest in PCL repair as well.…”
Section: Discussionmentioning
confidence: 99%